2017
DOI: 10.1016/j.drugpo.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Increases in synthetic cannabinoids-related harms: Results from a longitudinal web-based content analysis

Abstract: Background Synthetic Cannabinoid Receptor Agonists (SCRA), also known as “K2” or “Spice,” have drawn considerable attention due to their potential of abuse and harmful consequences. More research is needed to understand user experiences of SCRA-related effects. We use semiautomated information processing techniques through eDrugTrends platform to examine SCRA-related effects and their variations through a longitudinal content analysis of web-forum data. Method English language posts from three drug-focused w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 76 publications
(92 reference statements)
0
29
0
1
Order By: Relevance
“…Much coverage also focuses on poisonings, in which the main focus is adverse effects and not general effects. Despite the lack of academic literature focusing on the effects of these drugs, rich descriptions can often be located on online message forums such as BlueLight, in which “psychonauts” (those who explore altered states of consciousness through various drugs; Orsolini et al, ) and other individuals post reports describing their experiences (Enghoff & Aldridge, ; Lamy et al, ). Other rich sources of information are the seminal works authored by Dr. Alexander Shulgin and Ann Shulgin: Phenethylamines I Have Known and Loved (PiHKAL) and Tryptamines I Have Known and Loved (TiHKAL) (Shulgin & Shulgin, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Much coverage also focuses on poisonings, in which the main focus is adverse effects and not general effects. Despite the lack of academic literature focusing on the effects of these drugs, rich descriptions can often be located on online message forums such as BlueLight, in which “psychonauts” (those who explore altered states of consciousness through various drugs; Orsolini et al, ) and other individuals post reports describing their experiences (Enghoff & Aldridge, ; Lamy et al, ). Other rich sources of information are the seminal works authored by Dr. Alexander Shulgin and Ann Shulgin: Phenethylamines I Have Known and Loved (PiHKAL) and Tryptamines I Have Known and Loved (TiHKAL) (Shulgin & Shulgin, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The purposes of the 21 articles were diverse and focused on identification, detection, extraction, and/or description of symptom terms, including adverse drug events (n=11) [16][17][18][19][20][21][22][23][24][25][26] ; comparison of ePAT to another data source (n=4), including a regulatory agency 27 , molecular database 28 , research study 29 , or EHR 30 ; content and/or sentiment analysis (n=3) [31][32][33] ; description of the patient experience (n=2) 34,35 ; and development of a classifier (n=1) 36 . Table 2 organizes each study purpose as well as data source, text type, number of documents, and number of users chronologically to assess overall trends.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of documents used for analysis ranged from 241 electronic messages 16 to greater than 1 million tweets 28 . The text type of these documents varied between studies but was typically comprised of short length text documents including tweets 17,18,20,24,[26][27][28]32 , message posts 16,36 , forum posts 19,[21][22][23] , and patient responses to prompts 35 . Seven studies reported the number of users 18,22,29,31,[34][35][36] .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sole keyword-based crawling suffers from low precision as well as low recall. For instance, obtaining tweets related to marijuana legislation [7] using its street name spice pulls irrelevant content about pumpkin spice latte and spice in food.…”
Section: Language Understanding Of Tweetsmentioning
confidence: 99%